momento cultural en la historia social - Ugarte Tellería, Javier (Huarte de San Juan. Geografía e Historia, 2015)
One of the axes of development of historiography displayed in the Institute of Social History Valentín de Foronda’s vicinity has been the one we could call (following Lynn Hunt) new cultural history. Not so much of a disruptive but the prolongation of the classic story across the social history as detected Lawrence Stone (1979). Echoing is made that recent thinking emphasizes the inter-subjectivity the communicative reason and structures of language and culture. Never giving up empiricism principles.
Keywords: Historiography; IHSVF; Lawrence Stone; empiricism; culture